Drug-biomembrane interaction studies : the application of calorimetric techniques - Pignatello, Rosario (Woodhead Publishing series in biomedicine., 2013)
The design and development of drugs and new pharmaceutical formulations require a full characterization of the chemical and physicochemical events occurring at the level of the single active ingredients or excipients, as well as their reciprocal interaction. Thermal analysis techniques are among the most widely used methods to achieve this; among them, the Differential Scanning Calorimetry (DSC) technique, in which the thermotropic behaviour of a single substance or mixtures is analyzed as a function of a controlled temperature program. DSC is an accurate and rapid thermo-analytical technique,